Passenger Service Evaluation In Port Bungus Savings Of Padang City West Sumatra Province - Febriansyah; Ferdinand Pusriansyah; Pratiwi Maharani (IWTJ : International Water Transport Journal, 2021)
West Sumatra (abbreviated as sumbar) is a province in Indonesia located on the island of Sumatra with Padang as its capital. West Sumatra Province is located along the west coast of Sumatra and a number of islands off its coast such as the Sikakap, Sikabaluan, Siberut, and Tua Pejat Islands which are called the Mentawai Islands. There are 4 crossing routes in the Bungus Bay Crossing Port that connect to the Mentawai Islands, namely Padang - Sikakap, Padang - Sikabaluan, Padang - Tua Pejat, and Padang - Siberut and the existence of this route is very important in an effort to support economic development in the West Sumatra Province. The method used to analyze the existing problems is the calculation of the level of conformity with the minimum service standard with existing conditions. Using Ministerial Regulation no PM 39/2015 concerning Passenger Service Standards. Standard of Passenger Service at the Bungus Bay Crossing Port Not in accordance with the Minister of Transportation Regulation number PM 39 of 2015 concerning Transportation Passenger Service Standards because the port only meets 39% of the conformity percentage, namely in the aspect of reliability / regularity in the sale and exchange of ship tickets in less time for each person. From 1 minute, in the comfort aspect, the Mushallah is available but does not meet the standards and in the security aspect, there are security officers wearing uniforms. Based on the analysis, it can be concluded that there are still indicators that are still lacking and must be improved in several aspects of service such as in the waiting room for passengers, bathrooms / toilets whose conditions and numbers do not meet standards, lighting at the port at night, prayer rooms which are still adjacent to canteens, fire fighting facilities, evacuation routes or gathering points and special facilities for persons with disabilities and breastfeeding mothers who still do not meet the Minimum Service Standard requirements.